2021
DOI: 10.1002/jssc.202000913
|View full text |Cite
|
Sign up to set email alerts
|

A strategy to comprehensively and quickly identify the chemical constituents in Platycodi Radix by ultra‐performance liquid chromatography coupled with traveling wave ion mobility quadrupole time‐of‐flight mass spectrometry

Abstract: Quick identification of the complex composition of traditional Chinese medicine only through liquid‐mass spectrometry technology is difficult. Especially the identification of isomers and co‐eluting compounds is even more difficult. In this study, an approach of multidimensional data modes based on ultra‐performance liquid chromatography coupled with traveling wave ion mobility quadrupole time‐of‐flight mass spectrometry was proposed to quickly and comprehensively identify the compounds in Platycodi Radix. Fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Due to the complexity of TCM, there are many components that have similar structure and polarity, resulting in approximately identical retention time in the column. To achieve complete separation, the acquisition mode HDMS E combined ion mobility separation technology has an advantage in the separation and identification for co‐eluting compounds [16]. Ion mobility separation can not only provide a second separation based on their charge state and shape/sizes in the gas phase but also increase the overall peak capacity and specificity of constituent analysis over those of conventional high‐resolution MS approaches.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the complexity of TCM, there are many components that have similar structure and polarity, resulting in approximately identical retention time in the column. To achieve complete separation, the acquisition mode HDMS E combined ion mobility separation technology has an advantage in the separation and identification for co‐eluting compounds [16]. Ion mobility separation can not only provide a second separation based on their charge state and shape/sizes in the gas phase but also increase the overall peak capacity and specificity of constituent analysis over those of conventional high‐resolution MS approaches.…”
Section: Resultsmentioning
confidence: 99%
“…Ion mobility spectroscopy (IMS) technique is an analytical technique that can ionize at ambient pressure and provides secondary separation after liquid phase separation [13]. In addition to generating high-precision MS data, IMS can also separate ions based on their size, shape, and charge [14], thereby achieving accurate identification of mixture components [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al chose a 2D-UPLC-IM-MS method to improve peak capacity and resolution when screening biomarkers that can distinguish ginseng from red ginseng. In order to improve the efficiency of metabolite characterization, it is necessary to develop the processing software containing a standard CCS value database . Wang et al identified many components in Lanqin Oral Liquid (a Chinese patent medicine) by UPLC-IM-QTOF-MS and automatic peak annotation driven by UNIFI software.…”
Section: Applications Of Im-ms For the Separation And Characterizatio...mentioning
confidence: 99%
“…PGn currently has more clinical applications than PGb, and this mostly stems from differences in the chemical components associated with the different environments in which they grow, which means that the quality of PG is also difficult to control. Furthermore, most studies examining the quality of PG have mainly analysed the chemical composition, active components, and pharmacological actions of these components 23–26 . However, few bioinformatics analyses examining the molecular mechanisms, differentially expressed genes (DEGs), and differentially accumulated metabolites (DAMs) of PG grown in different geographic regions have been conducted, and this has impeded the development and utilisation of PG.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, most studies examining the quality of PG have mainly analysed the chemical composition, active components, and pharmacological actions of these components. [23][24][25][26] However, few bioinformatics analyses examining the molecular mechanisms, differentially expressed genes (DEGs), and differentially accumulated metabolites (DAMs) of PG grown in different geographic regions have been conducted, and this has impeded the development and utilisation of PG. The molecular mechanisms of medicinal plants involve multiple targets, multiple pathways, and networked processes.…”
mentioning
confidence: 99%